A new compound Pt3Bi2S2 with superior performance for the hydrogen evolution reaction. Issue 64 (21st July 2021) - Fang, Yuqiang; Wang, Sishun; Lin, Gaoxin; Wang, Xin; Huang, Fuqiang
Abstract : A new compound Pt3 Bi2 S2 exhibits excellent hydrogen evolution performance and long-term stability, which is higher than that of Pt/C. Abstract : The exploration of efficient electrocatalysts for the hydrogen evolution reaction (HER) is beneficial to obtain renewable clean energy. Herein, a new parkerite-type compound Pt3 Bi2 S2 was synthesized, constructed by [PtBi4 S2 ] octahedra. The Bi 6p orbital electrons upshift the Pt 5d band to promote hydrogen adsorption. Moreover, the Bi–Pt orbital hybridization greatly improves the conductivity and accelerates the charge transfer during the electrocatalytic process. Hence, Pt3 Bi2 S2 exhibits a superior catalytic activity for the HER with a low overpotential of 61 mV (at j = 10 mA cm −2 ) and a Tafel slope of 51 mV dec −1 . In addition, Pt3 Bi2 S2 has higher stability than commercial Pt/C. This work proposes a promising strategy for designing new excellent HER catalysts.